Rodzina von Stentsch - właściciele Przytoku w XVI-XIX wieku = Von Stentsch family - the owners of Przytok in 16th-19th centuries - Konopnicka, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the beginning of the early modern period the village of Przytok, located in Zielona Góra weichbild, was owned by von Burgsdorff family, then von Tschammer family, and in 1591 it was sold to Joachim von Stentsch. The history of this village was connected with the history of the family until the beginning of the 19th century.
Keywords: Śląsk, Dolny - historia; Stentsch; szlachta śląska; Przytok (pow. zielonogórski) - historia; Silesia; Silesian nobility